Preparation, mechanical and tribological properties of WC-Al2O3 composite doped with graphene platelets. Issue 8 (1st June 2020) - Zhang, Xiaoxiao; Zhu, Shigen; Shi, Tianyu; Ding, Hao; Bai, Yunfeng; Di, Ping; Luo, Yilan
Abstract: Advanced mechanical and tribological properties are the premises for the novel WC-Al2 O3 ceramic composite without metallic binder phase to be industrially applied. For this purpose, 0.3 wt% graphene platelets were doped during the fabrication of WC-Al2 O3 ceramic composite in this work. Characterization showed graphene platelets were homogeneously distributed in the ceramic matrix. Graphene platelets additions refined the grain size, increased the hardness (from 16.18 to 18.34 GPa) and fracture toughness (from 8.08 to 11.02 MPa m 1/2 ). Graphene platelets additions reduced the friction coefficient (from 0.47 to 0.28, under 40 N; from 0.57 to 0.38, under 60 N) and the specific wear rate (from 1.21 × 10 −5 to 1.32 × 10 −6 mm 3 N − 1 m −1, under 40 N; from 2.18 × 10 −5 to 6.72 × 10 −6 mm 3 N − 1 m −1, under 60 N), based on the ball-on-disk dry sliding.